The relationship between areas of life satisfaction, personality, and overall life satisfaction: An integrated account - Malvaso, Antonio; Kang, Weixi (Frontiers in Psychology, 2022)
A substantial amount of research has been conducted using a variety of methodological approaches to determine what influences life satisfaction. The bottom-up theory considers overall life satisfaction as a function of various areas of life satisfaction, whereas the top-down theory considers the areas of life satisfaction as a function of dispositional factors such as personality. We examined these models in a large-scale United Kingdom survey. Consistent with other studies, we found that both the bottom-up and top-down models of life satisfaction are supported in the United Kingdom by demonstrating that demographics, areas of life satsifaction, and personality traits can explain a significant portion of variances in overall areas of life satisfaction. We propose that future studies in life satisfaction research should consider the integrated account of life satisfaction rather than a unitary bottom-up or top-down perspective.